High Le Fort I osteotomy for correction of mid‐face deformity in Crouzon syndrome. (September 2016) - Nakajima, Yasumichi; Nakano, Hiroyuki; Sumida, Tomoki; Yamada, Tomohiro; Inoue, Kazuya; Sugiyama, Goro; Mishima, Katsuaki; Mori, Yoshihide
Abstract: An 18‐year‐old woman with mild Crouzon syndrome was referred with malocclusion and mandibular protrusion. Examination revealed Class III canine and molar relationships, hypoplastic maxilla, 1‐mm overbite, and −2‐mm overjet. Analysis showed 69° sella‐nasion‐A, 73.6° sella‐nasion‐B, and −4.6° A point‐nasion‐B point angles. Polysomnography revealed respiratory disturbance and 6.3% oxygen desaturation indices of 5.4/h and 9.0/h. We performed double‐jaw surgery using high Le Fort I osteotomy and bilateral sagittal split ramus osteotomy for midfacial deformity correction. Twelve months post‐surgery, her measures were 70.8°, 72°, −1.2°, 3.0/h, and 6.1/h, respectively. Esthetics were satisfactory. High Le Fort I osteotomy is effective for midfacial deformity correction in patients with Crouzon syndrome.